USA - Sandner, H. (Olympische Sommerspiele 2000 - Zur Entwicklung ausgewählter nationaler Spitzensportkonzepte und deren Umsetzung in Vorbereitung auf die Olympischen Spiele in Sydney, 2000)
On the development of the national system of elite and youth sport, it's practical application in the preparation for the Sydney 2000 Olympic Games, and the results of the US team at the Sydney games.